THE POSITION AND FUNCTIONS OF LOCAL REGULATIONS (DISTRICT REGULATION) DISTRICT/MUNICIPALITY AS AN INSTRUMENT OF REGIONAL AUTONOMY WITHIN A SYSTEM OF LEGISLATION IN INDONESIA - -, Jumadi (Journal of Humanity, 2016)
General understanding of the law indicates that the product areas that are made bythe local government, in no way can be separated from the system perundamginvitationnationally. Local regulations made by independent government units(autonomous) and Environment Authority an independent anyway. Therefore, doneagainst higher level legislation should not be solely based on pertingkatan, but ratheron the environment authority. in Indonesia is beside as further the elaboration oflegislation on it which produces district regulation delegasian, as well as the specialconditions in passenger areas that generate self-contained district regulation.